Carnosine Mitigates Manganese Mitotoxicity in an In Vitro Model of Isolated Brain Mitochondria - Ghanbarinejad, Vahid (Adv Pharm Bull, 2019)
Purpose: Manganese (Mn) is a neurotoxic chemical which induces a wide range of complications in the brain tissue. Impaired locomotor activity and cognitive dysfunction are associated with high brain Mn content. At the cellular level, mitochondria are potential targets for Mn toxicity. Carnosine is a dipeptide abundantly found in human brain. Several pharmacological properties including mitochondrial protecting and antioxidative effects have been attributed to carnosine. The current study aimed to evaluate the effect of carnosine treatment on Mn-induced mitochondrial dysfunction in isolated brain mitochondria. Methods: Mice brain mitochondria were isolated based on the differential centrifugation method and exposed to increasing concentrations of Mn (10 µM-10 mM). Carnosine (1 mM) was added as the protective agent. Mitochondrial indices including mitochondrial depolarization, reactive oxygen species (ROS) formation, mitochondrial dehydrogenases activity, ATP content, and mitochondrial swelling and permeabilization were assessed. Results: Significant deterioration in mitochondrial indices were evident in Mn-exposed brain mitochondria. On the other hand, it was found that carnosine (1 mM) treatment efficiently prevented Mn-induced mitochondrial impairment. Conclusion: These data propose mitochondrial protection as a fundamental mechanism for the effects of carnosine against Mn toxicity. Hence, this peptide might be applicable against Mn neurotoxicity with different etiologies (e.g., in cirrhotic patients).